A-120 Cognitive Function and VO2max following HIIT Exercise Intervention. (17th August 2022) - Myers, Terina L; Norling, Amani; Gerstenecker, Adam; Buford, Tom; Lazar, Ronald M
Abstract: Objective: To determine if an 8-week HIIT exercise intervention would improve VO2max and cognitive function in older sedentary women. Method: Eleven women between the ages of 60 and 75 participated in an 8-week HIIT exercise intervention. At baseline, participants were administered a VO2max test and a neuropsychological battery, which assessed both global functioning as well as specific domains of processing speed, visual memory, attention, language and executive function. Composite scores for each domain were calculated using average z-scores. Procedures performed at baseline were conducted again following intervention. Results: Following the intervention, there was a mean VO2max increase of 3.89 ml/kg/min (p<.0001) compared to baseline. Cognitive data showed the total cognitive composite z-score significantly improved from baseline (M=-0.71, SD=0.58) to follow-up (M=0.20, SD=0.61). Visual memory baseline (M=-0.37, SD=1.97) also showed significant increase at follow-up (M=0.27, SD=0.83) along with a language domain improvement from baseline (M=-0.04, SD=0.60) to follow-up (M=0.25, SD=0.59), all p <.05. In addition, VO2max was significantly correlated with the total cognitive composite z-score (r= 0.65; p< .05) and visual memory (r=.66; p<.05). Conclusions: We found that 8-weeks of HIIT was sufficient to increase VO2max in older sedentary women. Total composite z-scores and specific domains of visual memory and language also showed significant improvement after intervention. Total cognitive composite scores and visual memory were also correlated with VO2max. These findings highlight the need to explore further the mechanisms that drive exercise effects on cognition across diverse populations.